Functional Properties of Alstonia scholaris Seed Protein Isolates - Dutta, Mita; Laskar, Subrata; Dutta, Pinak (Asian Journal of Chemistry, 2014)
Functional properties of total protein isolate (TPI) prepared from Alstonia scholaris seeds were investigated. The moisture content and ash content of total protein isolate were found to be 9.13 and 2.12 % respectively. The protein contents of the seed protein concentrate was found to be 68.93 %. The minimum protein solubility was observed at pH 4 and maximum at pH 12. Oil- and water-holding capacities of the seed protein concentrate were 6.21 and 3.75 g/g respectively. The emulsifying activity and emulsion stability as well as foaming capacity and foam stability were greatly affected by pH. Lower values were observed at slightly acidic pH (pH 4). Total protein concentrate was moderately viscous and dependent on concentration. Viscosity was also affected by increased pHs. The lowest gelation concentration of the seed protein concentrate was found to be 14 % when protein was dissolved in distilled water.